Big Book Storytelling: Stimulation Strategies in Early Childhood Literacy - Siti Labiba Kusna; Endang Puspitasari (Institut Agama Islam Negeri Madura, 2023)
Background: Early childhood literacy plays an important role in overall personality development. Literacy can be developed in various ways, one of which is by using various interesting learning tools such as big books and storytelling. Aim: The purpose of this research is to analyze the application of big book storytelling media to early childhood literacy. Method: The type of research is experimental research with a one-group-pretest-posttest design. In the sampling technique, purposive sampling was used. The research was conducted at TK Negeri Pembina Ngimbang, Lamongan Regency with a total sample of 85 children. Data collection techniques used observation sheets and documentation. The data analysis technique used the Wilcoxon Test. Result: The results of the Wilcoxon test mean the rank between the pretest and posttest is 9.50, with a Z of -4.243 and a significance of 0.000 <0.05 indicating that there is a significant difference between the pretest and posttest. Conclusion: The results of this study big book storytelling media can stimulate early childhood literacy. This has implications that PAUD educators can maximize the use of big book storytelling media to increase early childhood literacy.